The Relationship Between Suicide Attempts and Menstrual Cycles in the Emergency Department and the Sociodemographic and Clinical Characteristics of These Patients - Yılmaz Zengin; Mustafa Çalık; Fatih Büyükcam; Jale Şen; Şenay Akpınar; Ahmet Burak Erdem; Ahmet Ceylan; Öner Odabaş (Eurasian Journal of Emergency Medicine, 2015)

(untitled)
Aim: Suicidal behavior is defined as choosing death in the conflict between life and death. The aim of this study is to investigate the suspected relationship between suicide attempts and menstrual cycles and to evaluate the sociodemographic and clinical characteristics of the non-pregnant female patients of reproductive age who have presented to our hospital after attempting suicide.Materials and Methods: In this study, 102 female patients (aging 16–45 years) of reproductive age with regular menstrual cycles who presented to the emergency department because of suicide attempts were enrolled. The study was designed as prospective, cross-sectional, and descriptive. The patients’ sociodemographic, clinical, and laboratory biochemical parameters were recorded. For the purposes of this study, 100 healthy women who fulfilled the criteria formed the control group and underwent the same procedures as the patient group.Results: Among the patients who presented to the hospital after attempting suicide, 64 (62.7%) were in their menstrual period, six (5.9%) were outside their menstrual period during the follicular phase, five (4.9%) were at the mid-cycle peak, and 27 (26.4%) were at the luteal phase, as determined on the basis of the date of their last menstrual period and their blood hormone levels.Conclusion: The majority of suicide attempts by women occurred during their menstrual period when the estradiol and progesterone levels are at their lowest.